DETECCIÓN DE ANTICUERPOS CONTRA Lawsonia intracellularis EN PORCINOS PROVENIENTES DE GRANJAS TECNIFICADAS DEL VALLE DE LIMA Y HUARAL - Valdez C., María (2002)
The aim of the present study was to detect antibodies against Lawsonia intracellularis in pigs from well-managed farms in Lima and Huaral valleys. Antibodies were detected using the indirect immunofluorescence test in 197 serum samples from pigs of three different ages. 38.7% of the samples were positive, corresponding 18.9, 44.3 and 45.5% to farms located in the areas of Huaraz, Cieneguilla and Lurín, respectively. The prevalence recorded in weaned and fattened pigs, and gilts were 24.6, 47.6 y 44.7%, respectively. The presence of antibodies indicates that these pigs have been exposed to the bacteria, so Lawsonia intracellularis should be considered as a new microorganism causing diarrhea and therefore, affecting the pig industry in the country